A Choice-based conjoint analysis of social media picture posting and souvenir purchasing preference: A case study of social analytics on tourism. Issue 6 (November 2021) - Zhang, Jiahao; Wei, Xindong; Fukuda, Hiroatsu; Zhang, Li; Ji, Xiangnan
Highlights: Tourists with different frequency of posting trip pictures (PTP) on social media always have different souvenir purchasing preferences. If tourists' PTP frequency rise, their souvenir preferences for "Availability" will increase, and the preferences for "Uniqueness" will decrease. With the increase in the frequency of tourists' PTP, their willingness to pay (WTP) for souvenirs exhibiting high availability rises significantly, and note that the highest is the tourists (Always PTP) with the WTP reaching US35.39. With the decrease of tourists' PTP frequency, their WTP for the medium level of the souvenir attribute "Uniqueness" fluctuates around US15, and the WTP for the high level of "Uniqueness" rises to US 36.42 continuously. Abstract: Over the past few years, increasing tourists have generated interest in social media and shared their trip pictures and experience on it. As revealed from existing studies, tourists' preference of posting pictures of their trip on a social media site(s) may be associated with their purchasing behaviors. In the present study, Choice-based Conjoint Analysis (CBCA) was conducted to examine tourists' souvenir preferences based on various frequencies for posting trip pictures (PTP). As indicated by result that tourists exhibiting a higher PTP frequency are more inclined to purchase souvenirs of higher availability. Furthermore, the group of tourists exhibiting the highest PTP frequency reported the highest willingness to pay (WTP) for the souvenir with a high level of "Availability", while tourists with the lower PTP frequency are inclined to purchase souvenirs exhibiting higher uniqueness. The present study is recognized as one of the initial attempts to cross-pollinate the research streams of souvenir purchase behavior and social media usage. The mentioned findings suggest that producers and sellers are required to adjust souvenir promotion and design by complying with the PTP data.